2021
DOI: 10.3390/educsci11110671
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Students’ Industrial Internship Experience Perception and Satisfaction: Work Experience Scale Validation

Abstract: An essential aspect of higher education institutions’ academic curricula for engineering courses is the students’ industrial internship programs. In the literature, it is well accepted that such programs provide valuable learning outcomes and increase the graduates’ employment prospects. Thus, it is paramount to evaluate the internship programs’ quality to identify opportunities to improve their design and implementation. However, that evaluation typically depends on self-designed academic assessment surveys o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
0
0
1
Order By: Relevance
“…Evaluando las percepciones sobre las experiencias de las prácticas profesionales, Nogueira et al, (2021) proponen la validación de la satisfacción de estudiantes de ingeniería que participaron en programas de pasantía industrial ofrecidos por universidades públicas y escuelas tecnológicas en Portugal mediante una herramienta adaptada del Work Experience Questionnaire (WEQ), los resultados de este estudio señalaron que la resolución de problemas fue la competencia mejor desarrollada por los estudiantes durante sus prácticas profesionales.…”
Section: Estado Del Arteunclassified
“…Evaluando las percepciones sobre las experiencias de las prácticas profesionales, Nogueira et al, (2021) proponen la validación de la satisfacción de estudiantes de ingeniería que participaron en programas de pasantía industrial ofrecidos por universidades públicas y escuelas tecnológicas en Portugal mediante una herramienta adaptada del Work Experience Questionnaire (WEQ), los resultados de este estudio señalaron que la resolución de problemas fue la competencia mejor desarrollada por los estudiantes durante sus prácticas profesionales.…”
Section: Estado Del Arteunclassified
“…Then, the perception related to the experiments was explored by applying surveys monitoring the learners' previous background with online laboratories, their expectations, and their sense of accomplishment at the end of all the sessions. The answers provided were statistically treated and analyzed, considering the evidence of associations between the learning quality and the perceptions described by the CEQ (Course Experience Questionnaire) scales [32][33][34].…”
Section: Overviewmentioning
confidence: 99%
“…In the Work Experience Questionnaire (WEQ) 1 where 447 engineering students from Portuguese public universities and polytechnic schools participated, the effectiveness of industrial internship for engineering students was demonstrated. As the result of the internship, most students not only gained the technical competence but also non-technical abilities such as teamwork skills and positive attitudes and readiness into the world of work (Teresa Nogueira, 2021).…”
Section: The Role Of Industrial Training In Engineering Educationmentioning
confidence: 99%